1965
DOI: 10.1037/h0021698
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral biophysics.

Abstract: Electromagnetic energy is an important factor in the biophysical analysis of the properties and function of living systems. Due to technical advances in electronics, this energy is now being used as a research tool, both by study of its emission by living organisms and also by applying it to the organism. In this paper, the nature of the energy is sketched. Then, data on fingertip detection of color, neural emission of infrared energy, the use of electron paramagnetic resonance techniques to detect neural acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…There is an impressive list of references concerning the effects of electromagnetic radiation on animals and humans, including ArehartTreichel (1974) and Frey (1965) as well as the following studies. Some of these effects include changes in EEC frequency and amplitude (in rabbits) (Livanov, Tsypin, Grigor'ev, Kruschehev, Stepanov, & Anav'ev 1960, Kholodov 1963, subnormal EEC activity in a group of 120 people who had been exposed for more than one year to electromagnetic energy in the centimeter wavelengths (Edelwejn & Haduch 1962), nervous exhaustion with irritability (Sadchikova & Orlova 1958), and, in some instances, abnormal slowness of the heartbeat (Edelwejn & Haduch 1962, Sadchikova & Orlova 1958, Kevork'ian 1948, Presman 1962a, 1962b and increased incidence of reports of headache at the end of the work day along with sleep disturbance and memory change (Kt^vork'ian 1948).…”
Section: In the Period Between September 1973 And June 1974 A Team Omentioning
confidence: 99%
“…There is an impressive list of references concerning the effects of electromagnetic radiation on animals and humans, including ArehartTreichel (1974) and Frey (1965) as well as the following studies. Some of these effects include changes in EEC frequency and amplitude (in rabbits) (Livanov, Tsypin, Grigor'ev, Kruschehev, Stepanov, & Anav'ev 1960, Kholodov 1963, subnormal EEC activity in a group of 120 people who had been exposed for more than one year to electromagnetic energy in the centimeter wavelengths (Edelwejn & Haduch 1962), nervous exhaustion with irritability (Sadchikova & Orlova 1958), and, in some instances, abnormal slowness of the heartbeat (Edelwejn & Haduch 1962, Sadchikova & Orlova 1958, Kevork'ian 1948, Presman 1962a, 1962b and increased incidence of reports of headache at the end of the work day along with sleep disturbance and memory change (Kt^vork'ian 1948).…”
Section: In the Period Between September 1973 And June 1974 A Team Omentioning
confidence: 99%
“…for all practical purposes all humans emit radiation in the long-wavelength infrared region as if they were 'black bodies' " (p. 873).s Frey, commenting on Youtz's results (see below) noted that electromagnetic radiation from an observer's fingers, which are in a lightproof box with colored chips, would illuminate these chips with infrared energy. 4 Barnes reported that because people's skin is relatively transparent to light as well as radiation in the infrared range shorter than about 2 pm, the skin's pigmentation ". .…”
Section: Infrared Radiationmentioning
confidence: 99%
“…For instance, the studies of Frey [1,2], Guy and Chou [3] have shown that the interaction between microwaves and dielectrics generally produces acoustic waves due to a sudden temperature rise that occurs within the irradiated area. Later on, some papers have undertaken further studies in analyzing the acoustic waves generated in solids by thermal effects from Laser impact [4,5] or by microwave irradiations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%